2020
DOI: 10.20511/pyr2020.v8nspe3.659
|View full text |Cite
|
Sign up to set email alerts
|

Accesibilidad, dificultades y ventajas del estudio online por COVID-19 en un posgrado presencial en educación

Abstract: En este trabajo se presentan los resultados de una investigación realizada con estudiantes de un posgrado presencial en Ciencias de la Educación sobre la valoración de cursos virtuales durante el distanciamiento físico por COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 15 publications
1
8
1
4
Order By: Relevance
“…However, Chiecher et al (2005) highlight the existing educational gap given the unequal and inequitable availability of resources among students, which allow them to integrate and give continuity to the virtual teaching-learning process in the face of this emergency (Altuzarra, Gálvez and González, 2018;Armitage and Nellums, 2020;Cáceres, Jiménez and Martín, 2020;Orgaz, Moral and Domínguez, 2018;Sánchez, et al, 2020). In line with the latter, the study by Bazán et al (2020) shows that online courses are highly valued by students with advantages of accessibility and connectivity, as they perceive less difficulty in the management of resources by teachers. Chiecher et al (2005) carried out a comparative study between a face-to-face and a mixed group, in the results of which positive perceptions were obtained in the group that included the virtual modality.…”
Section: Introductionmentioning
confidence: 87%
“…However, Chiecher et al (2005) highlight the existing educational gap given the unequal and inequitable availability of resources among students, which allow them to integrate and give continuity to the virtual teaching-learning process in the face of this emergency (Altuzarra, Gálvez and González, 2018;Armitage and Nellums, 2020;Cáceres, Jiménez and Martín, 2020;Orgaz, Moral and Domínguez, 2018;Sánchez, et al, 2020). In line with the latter, the study by Bazán et al (2020) shows that online courses are highly valued by students with advantages of accessibility and connectivity, as they perceive less difficulty in the management of resources by teachers. Chiecher et al (2005) carried out a comparative study between a face-to-face and a mixed group, in the results of which positive perceptions were obtained in the group that included the virtual modality.…”
Section: Introductionmentioning
confidence: 87%
“…También se coincide con lo señalado por Bazán-Ramírez et al (2020) en lo que respecta a que, para el nivel de posgrado, el alumnado se enfrentó a diversas situaciones logísticas y afectivas durante el confinamiento, lo que influyó su vida laboral, académica y personal. Del mismo modo, se confirma lo señalado por Cabero y Llorente (2020) en lo que concierne a que el aprendizaje generado a través del flipped classroom 14 fue posible mediante el empleo de las herramientas tecnológicas, que permitió una relación síncrona y asíncrona entre docente-discente.…”
Section: Discusión Y Conclusionesunclassified
“…Específicamente en el nivel posgrado, la mayoría del estudiantado labora y se financia sus estudios con sus propios recursos, lo que complejiza la situación de la pandemia debido a que para continuar con su formación académica es necesario contar con conectividad y recursos tecnológicos, ya que el alumnado trabaja desde el hogar, en donde confluyen diversas situaciones tales como atender a la familia, compartir el dispositivo tecnológico entre los miembros e incluso resolver el problema de contagio en un familiar, entre otras (Bazán-Ramírez et al, 2020). Lo anterior ha generado diversas experiencias en el estudiantado a medida que se ha desarrollado la pandemia, lo que ha evidenciado la necesidad de poseer competencias de tipo digital, emocional y social, debido a que se enfrentan a trabajar y aprender en contextos no-tradicionales y con el uso de plataformas y herramientas tecnológicas, las cuales requieren una formación específica para su manejo (Cabero y Llorente, 2020).…”
Section: Introductionunclassified
“…Various studies have reported on the effects of student connectivity and accessibility to the internet and to other technological gadgets, of teacher's skills for technological resources and online classes, as well as of student self-teaching/learning skills, on the assessment of advantages and the effectiveness of postgraduate online courses during the pandemic [6][7][8][9][10]. Thus, during the pandemic, students have valued remote learning, comfortability, user-friendliness, accessibility, and student-centered education as important advantages of online classes.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have reported on the diversity of situations that affect students in medical training. Literature on this topic is significant, has been reported from different parts of the world [6,[18][19][20][21][22][23][24][25][26], and continues to grow. However, for specialization teaching or postgraduate contexts (like medical residency programs), the effect of virtual classes may be more harmful than good for student health because of the demands of their professional activity and the long hours that they have to spend in a hospital.…”
Section: Introductionmentioning
confidence: 99%